2016
DOI: 10.1007/s12265-016-9716-y
|View full text |Cite
|
Sign up to set email alerts
|

Rad-deletion Phenocopies Tonic Sympathetic Stimulation of the Heart

Abstract: Sympathetic stimulation modulates L-type calcium channel (LTCC) gating to contribute to increased systolic heart function. Rad is a monomeric G-protein that interacts with LTCC. Genetic deletion of Rad (Rad−/−) renders LTCC in a sympathomimetic state. The study goal was to use a clinically inspired pharmacological stress echocardiography test, including analysis of global strain, to determine whether Rad−/− confers tonic positive inotropic heart function. Sarcomere dynamics and strain showed partial parallel i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 32 publications
(59 reference statements)
2
23
0
Order By: Relevance
“…Nevertheless, function in the Rad −/− mice appears to be sufficiently preserved to avoid the precipitous drop in cardiac output and blood pressure observed in WT mice ( Figure 3 ). This acute preservation of function occurs prior to scar spread and myocardial remodeling, suggesting that the improved inotropy associated with Rad deletion 12 , 27 is maintained after AMI. In WT mice after MI, loss of function results in reflexive, tonic elevation of sympathetic drive that causes pathological cardiomyocyte remodeling.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Nevertheless, function in the Rad −/− mice appears to be sufficiently preserved to avoid the precipitous drop in cardiac output and blood pressure observed in WT mice ( Figure 3 ). This acute preservation of function occurs prior to scar spread and myocardial remodeling, suggesting that the improved inotropy associated with Rad deletion 12 , 27 is maintained after AMI. In WT mice after MI, loss of function results in reflexive, tonic elevation of sympathetic drive that causes pathological cardiomyocyte remodeling.…”
Section: Discussionmentioning
confidence: 95%
“…The Rad −/− heart has stable elevated function compared with WT 12 , 27 . This functional gain is preserved 24 h after LAD ligation, although there is a parallel reduction of function in both Rad −/− and MI ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, Rad null mice of advanced age (18 months) exhibited an increased rate of SR Ca 2+ uptake via SERCA2a that the authors interpreted as a contributing mechanism to the observed cardioprotective phenotype . More recent work has shown the preservation of inotropic function through more efficient sarcomeric function in Rad null mice . As Rad expression was found to be decreased in non‐ischaemic failing human myocardium by Western blot, the authors of this latter study proposed that the downregulation of Rad in the hearts of these patients was a sympathomimetic compensatory mechanism to increase cardiac output.…”
Section: Relevance Of Rgk Proteins In Heart Functionmentioning
confidence: 94%
“…Rad-knockout mice display an increased maximum Ca 2+ current, and the Ca 2+ channels activate at lower voltages, mimicking the effects of βadrenergic receptor stimulation [66,67]. Other studies, however, led to expectations that Rad is not directly involved in adrenergic regulation of Ca V 1.2 since adenoviral-induced overexpression of Rad [68] and Rem [69] in cultured cardiomyocytes ablated Ca V 1.2 and attenuated adrenergic regulation.…”
Section: Rad Is the Pka Targetmentioning
confidence: 99%